An exploratory study into the use of faceted classification for emotional words. - Heok, Adrian Kay Heng. (2008)
This project is an exploratory study into the use of faceted classification for categorizing emotional words. The motivation for this endeavor is that it has never been attempted before. A useful lexicon of emotional words rated to reveal its polarity, intensity and variability quotient would result. Also, the methodology prescribed could act as a reference for future study to peg other matters as elusive as emotions numerically, thereby making it capable of being processed by machines.